Chemical composition, antimicrobial activities, and molecular docking studies of Turkish propolis ethanol extract - Ozbey, Gokben; Muz, Mustafa Necati; Tanriverdi, Elif Seren; Erkan, Sultan; Bulut, Niyazi; Otlu, Baris; Zigo, Frantisek (Czech Academy Agricultural Sciences, 2023)
The purpose of the present study was to investigate the antimicrobial effect of propolis ethanol extract col-lected from the Tarsus district of Mersin province, Kilis province, Yayladagi district of Hatay province in southern Turkiye and Sarkoy district of Tekirdag province of northwestern Turkiye against Escherichia coli (ATCC 25922), Helicobacter pylori (ATCC 43504), Pseudomonas aeruginosa (ATCC 27853), and Staphylococcus aureus (ATCC 29213). Their chemical constituents were detected via liquid chromatography-mass spectrometry/mass spectrometry (LC-MS/MS). They were used in a molecular docking approach to search the interactions between the propolis compounds. A total of 24 phenolic compounds were detected in all samples. 3-4 dimethoxycinnamic acid, caffeic acid and genistein were indicated to be the predominant phenolic compounds in propolis extracts by LC-MS/MS, while rutin was found in the lowest concentra-tion. Phenolic compounds were detected in a high concentration of the propolis samples collected from the Tarsus dis-trict of Mersin province. The broth microdilution method determined minimum inhibition concentration (MIC) values. MIC values ranged from 0.02 to 14 mg center dot mL-1. E. coli and S. aureus examined were as susceptible to the propolis extracts ex-cept for Mersin and Tekirdag propolis samples. The propolis sample collected from the Tarsus district of Mersin province presented the highest antibacterial activity on P aeruginosa with MIC values of 1 mg center dot mL-1. Active substances in propolis were docked to the relevant target proteins (5LMM, 4NX9, 5YHG, and 5FXT) representing E. coli (ATCC 25922), H. py-lori (ATCC 43504), P aeruginosa (ATCC 27853), and S. aureus (ATCC 29213), and with the help of molecular simulation. With this study, we indicated that the ethanol extract of propolis had a stronger antibacterial activity on S. aureus isolates than that of E. coli, H. pylori, and P aeruginosa. Although each component of propolis contributed to the antibacterial activity, the contribution of the vitexin component to the antibacterial activity was found to be quite significant.
Keywords: antimicrobial effect; minimum inhibition concentration (MIC); phenolic compounds; vitexin; liquid chro-matography-mass spectrometry; mass spectrometry (LC-MS; MS)